A Systematic Literature Review Women Leadership in Police - Oetari Poernamasasi, Ida (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
A Systematic Literature Review on women’s leadership in Policing aims to provide insight into how women in leadership in several countries in the world. The issue of women in the police becomes important along with the concept of gender equality in police organizations which are dominated by men. Women must try to get roles in the police, including becoming leaders, despite the various challenges they face. This research uses secondary data based on the results of a study conducted in the 2009-2023 period. The method used is to examine articles/journals published via Google Scholar, Emerald and Semantic Scholar. The results of the SLR show that from 2009 - 2023 women are still struggling to become leaders in the police because there is still discrimination, obstacles and gender prejudice in their careers. Career promotion still has subjective criteria that justify that male leadership candidates are ideal in the police. This finding is due to the police organizational culture being